Integrated Ecology Recreational Edu-Forest Sibuatan Center - Eddy, Firman; Harianja, Yose Alfredo Marganda (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The tourism sector is crucial to Indonesia's economy, especially in the Sibuatan Forest Area, Merek Subdistrict, Karo Regency. However, ecosystem degradation and a lack of public awareness about forest conservation pose significant challenges. To address these, a holistic approach involves designing recreational facilities that integrate ecotourism, education, and ecological architecture. These facilities aim to protect and optimize the forest while inspiring, educating, and creating sustainable local economic opportunities, fostering harmony between humans and nature. The ecological architecture theme is chosen for its ability to blend buildings with the environment while maintaining sustainability and ecological balance. This approach also promotes using environmentally friendly materials to reduce the carbon footprint. Architectural design in the forest emphasizes minimizing environmental impact through recycled materials and sustainable technologies. Facilities will be strategically placed to avoid disrupting the ecosystem and biodiversity. This design enhances tourism appeal by providing an educational and sustainable ecotourism experience. Furthermore, this initiative is expected to raise local awareness about environmental conservation and create new economic opportunities through tourism. Ultimately, the community will benefit from environmental preservation efforts and sustainable economic development in the protected forest area.